ANALISIS ARAH DAN KEBIJAKAN PENGEMBANGAN PERPUSTAKAAN IAIN CURUP MENGHADAPI ERA INDUSTRI 4.0 - Rhoni Rodin; Mulliati Mulliati (Ikatan Pustakawan Indonesia, 2019)
The purpose of this paper is to analyze the direction and policy of developing the IAIN Curup’s Library facing the industrial era 4.0. This type of research is qualitative, using a descriptive approach. Data collection techniques using surveys, interviews and documentation. While the data analysis using analytic qualitative descriptive techniques. The results showed that there were several directions and policies carried out and prepared by the IAIN Curup’s Library in the face of era 4.0, namely the first, collection service policies and directions, through increasing digital collections and developing library services for accessing digital collections, developing access to resources open learning or open educational resources, increasing collaboration with other libraries to expand access to information; second, the direction and policy of facilities and infrastructure, through adding library facilities for wider access to electronic information sources. Includes: adding servers, adding PCs, and access points, and increasing internet capacity or bandwidth; third, the direction and policy of human resources, through encouraging librarians to participate in the Development of Sustainable Competency Competencies or PKB. Both those held locally, regionally, nationally and internationally, conduct research or scientific studies on librarianship, and comparative studies between libraries; fourth, good management direction and policy, through the development of a standard-based library management system and accreditation at the National Standards of University’s Library reference No. 13 of 2017 also other standards such as IFLA, compiling standard operating procedures, and making library development strategic plans.